2020
DOI: 10.3390/nu12051398
|View full text |Cite
|
Sign up to set email alerts
|

It’s No Has Bean: A Review of the Effects of White Kidney Bean Extract on Body Composition and Metabolic Health

Abstract: The rising prevalence of overweight and obesity is a global concern, increasing the risk of numerous non-communicable diseases and reducing quality of life. A healthy diet and exercise remain the cornerstone treatments for obesity. However, adherence rates can be low and the effectiveness of these interventions is often less than anticipated, due to compensatory changes in other aspects of the energy balance equation. Whilst some alternative weight-loss therapies are available, these strategies are often assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
0
25
0
3
Order By: Relevance
“…Various previous studies have shown that seeds of kidney bean have α-amylase inhibitors inhibiting α-amylase activities in animals and insects, related to control type-2 diabetes mellitus by inhibition of DPP-IV, and a lectin called phytohaemoagglutinin could adjust the activity of glucagon-like peptides GLP-1 (glucagon-like peptide-1) [ 152 , 153 , 154 ]. The common bean P. vulgaris have three isoforms of α-amylase inhibitor including α-AI1 (known as phaseolamin), α-AI2, and α-AIL, which has been identified and tested in numerous clinical studies against α-amylase action [ 152 , 155 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…Various previous studies have shown that seeds of kidney bean have α-amylase inhibitors inhibiting α-amylase activities in animals and insects, related to control type-2 diabetes mellitus by inhibition of DPP-IV, and a lectin called phytohaemoagglutinin could adjust the activity of glucagon-like peptides GLP-1 (glucagon-like peptide-1) [ 152 , 153 , 154 ]. The common bean P. vulgaris have three isoforms of α-amylase inhibitor including α-AI1 (known as phaseolamin), α-AI2, and α-AIL, which has been identified and tested in numerous clinical studies against α-amylase action [ 152 , 155 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…There was a significant difference (p < 0.05) observed in the mean score of the BMI with SD in the PV group at 26.44 ± 2.7 and 26.36 ± 2.65. These antiadipogenic effects were proven by many other researchers [27,28].…”
Section: Effect On Bmimentioning
confidence: 83%
“…The placebo supplement contained functional ingredients, including white kidney bean extract, Psyllium husk, and Garcinia cambogia extract, which have been reported to modulate the gut microbiota in animals and humans ( 23 25 ). Therefore, the effect on weight loss could be expected in the placebo group ( 26 28 ). Our results indicated that the composition of the gut microbiota was altered differently in the placebo (functional ingredients) and probiotic (functional ingredients + probiotics) groups.…”
Section: Discussionmentioning
confidence: 99%